Fruits and Seeds Character of Moringa Oleifera Lam. Accession of Salut Village, North Lombok Regency - Miftahul Jannah; I Ketut Ngawit; Bambang Budi Santoso (Indonesian Journal of Applied Science and Technology, 2020)
The environment in which the plants grow and develop is thought to have an effect on the character of the fruit and seeds and the quality of the Moringa seeds, as well as affect the seeds germination, growth and adaptability of the seedlings. Characterization is one of the activities carried out in order to identify the properties of a Moringa accession to be used in further plant breeding programs. The research aimed to describe the character of fruit and seeds as well as the relationship of the accession in Salut Village, Kayangan District, North Lombok Regency, which is the center of the growth of Moringa trees in West Nusa Tenggara, using descriptive methods through surveys and sampling by purposive sampling and analyzed with the SPSS-20 program cluster analysis. The results show that there were significant differences in the morphological and physiological characters of Moringa seeds between accessions from Salut Village, North Lombok Regency. The accession of Moringa trees that have the closest relationship was Sambik Rindang-2 and Sambik Rindang-8 with a coefficient value of 2.44, while the farthest relationship was Sambik Rindang-1 and Tanak Sebang-6 with a coefficient value of 67.87.